Development of application for transporting things - BRAHIMI et ABLI, Rami et MOHAMMED ELAMIN (FACULTY OF MATHEMATICS AND INFORMATICS DEPARTMENT OF COMPUTER SCIENCE - OPTION: Information Systems and Software Engineering, 2020)
The objective of this work is to design and build a system that facilitates the transport of objects from one location to another. We proposed a solution that consists of developing an application for the transportation of people, goods and other objects. To design this application, we chose the UML language and for the development and realization, we opted for the Visual Studio Code and WampServer, and as language HTML,CSS,PHP,AJAX.
Keywords: Transport of people, transport of goods, web application, UML, charity.